RELATIONSHIP BETWEEN MANAGERIAL SKILLS AND EFFECTIVE MANAGEMENT OF SMALL AND MEDIUM ENTERPRISES IN BAUCHI METROPOLIS (NAU Journal of Technology and Vocational Education, 2025)
This study relationship between managerial skill and effective management of small and medium enterprises in Bauchi metropolis. The main purpose of the study was to determine the relationship managerial skill on effective management of small and medium enterprises in Bauchi metropolis. The study was guided by three objectives, with corresponding research questions and null hypotheses. Relevant literature related to the study was reviewed. The design for the study was descriptive survey. The population of the study comprised 263 Managers/owners of small and medium business enterprises. The researcher sampled 159 subjects using proportionate random sampling technique. The instrument for data collection was developed by the researcher from adaptation from the existing instruments; financial management skill; Marketing skill; Communication Skill; The instrument was validated by 4 experts. The instrument was tested and reliability coefficient of 0.80 was obtained. The research questions were answered using descriptive statistics (demographic, mean and standard deviation) while the hypotheses were tested using correlation analysis. The study revealed that financial management skill, has high skill relationship on effective management. Marketing skill; has moderate skill significance relationship on students’ for been self-reliant. Communication skill; has large extent influence on effective management. Based on the results, it was recommended, that parents should educate and encourage their children to be business-oriented upon; Stakeholders like managers/owners, Parents, government, NGO’s, and scholars should create public awareness programmes that will help to promote small and medium businesses from collapses, values, and beliefs that encourage business creations; The manager/owners should be encouraged to embrace  effective management or training in order for them to become self-reliant and wealth creators; The Government should make accessible loans available for manager/owners as they are doing now so as to start up their businesses; managerial skills and training should upheld, increase awareness and change the mind-set of the individual/managers/owners toward imbibing small and medium business enterprises culture and reduce over reliance on government.
Keywords: Managerial; skills; effective; small; enterprises